Overcoming mental health stigma through student’s awareness and project-based inclusive pedagogy in English teaching colleges: Moderating role of institutional support in China - Gao, Yuan (Frontiers in Psychiatry, 2022)
Mental health stigma undermines collaborative work and creates communication breakdowns for students to face real-world challenges. Moreover, project-based English learning in East-Asian nations is a significant challenge for advancing students’ effective learning, while students lack mental health self-awareness. Unawareness causes distractions and results in learning inefficiencies. Furthermore, without institutional support (IS) achieving effective learning could never be possible. Therefore, this study investigates the relationships between project-based learning (PBL) and mental health awareness (MHA) with effective English language teaching among university students in China. We also tested the moderation effect of IS in the relationships between PBL and MHA with effective English language learning (EEL). Using the purposive sampling technique, we collected valid responses from 713 students studying English as a foreign language in universities and colleges in Harbin, China. The findings interestingly supported the direct hypotheses between PBL and EEL, as well as MHA and EEL. Moreover, the moderating role of IS established a significant effect on both PBL and EEL, as well as MHA and EEL, respectively. Policymakers, practitioners, and academicians should understand that integrating PBL as an inclusive pedagogy method with proper IS may enhance effective learning; however, it will consume more time.